2022
DOI: 10.1093/infdis/jiac402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Molecular Mosprie Assay for Detection of Helicobacter pylori and Resistance to Clarithromycin and Levofloxacin

Abstract: Background Helicobacter pylori eradication regimens should be guided by antimicrobial susceptibility testing. The objective of this study was to evaluate the molecular-based Mosprie assay for detecting H. pylori resistance to clarithromycin and levofloxacin using gastric biopsies. Methods A total of 185 culture-positive frozen gastric biopsies were included for Mosprie assay and also for 23S rRNA and gyrA gene sequencing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Although it is generally believed that the detection of antibiotic resistance by molecular method and E-test method is highly consistent, some samples have been reported to be phenotypically resistant but genotypically sensitive, suggesting that some rare mutations associated with phenotypic resistance may be missed by molecular method. 12 A recent study demonstrated that the molecular testing-guided therapy was comparable to susceptibility testing-guided therapy in first-line treatment and non-inferior to susceptibility testing-guided therapy in third-line treatment, supporting the use of molecular testing-guided therapy for H. pylori eradication. 13 But the evidence for the use of genotypic resistance-guided therapy in eradicating H. pylori infection compared to conventional treatment regimens remains to be evaluated.…”
Section: Introductionmentioning
confidence: 93%
“…Although it is generally believed that the detection of antibiotic resistance by molecular method and E-test method is highly consistent, some samples have been reported to be phenotypically resistant but genotypically sensitive, suggesting that some rare mutations associated with phenotypic resistance may be missed by molecular method. 12 A recent study demonstrated that the molecular testing-guided therapy was comparable to susceptibility testing-guided therapy in first-line treatment and non-inferior to susceptibility testing-guided therapy in third-line treatment, supporting the use of molecular testing-guided therapy for H. pylori eradication. 13 But the evidence for the use of genotypic resistance-guided therapy in eradicating H. pylori infection compared to conventional treatment regimens remains to be evaluated.…”
Section: Introductionmentioning
confidence: 93%